Utilization of Coconut Shell and Coffee Grounds as Briquettes Using the Carbonization Method - Adhitasari, Alfiana; Manfaati, Rintis; Paramitha, Tifa; Zahwa, Keisya Adellia; Setiawan, Kiranna Shalmadevy; Yusuf, Yusmardhany (Eksergi, 2025)
Biomass-based briquettes offer a renewable energy alternative that can help reduce CO₂ emissions. Coconut shells and coffee grounds are promising waste materials due to their high calorific value. This study aimed to optimize the composition and carbonization time in producing briquettes from these two materials. The briquettes were prepared following SNI 01-6235-2000 and export briquette standards. The process included drying, carbonization at 300 °C for 60, 90, 120, 150, and 180 minutes, sieving, mixing, molding, and drying. Coconut shells and coffee grounds were mixed at weight ratios of 9:1, 8:2, 7:3, 6:4, and 5:5 with a total of 46.5 grams and 8.5 grams of adhesive. Briquette quality was evaluated based on moisture content, ash content, volatile matter, density, calorific value, and fixed carbon. The 9:1 composition yielded the highest calorific value of 6,472 cal/g, while a carbonization time of 90 minutes produced the best calorific value of 6,504 cal/g. The results show that a high proportion of coconut shells with limited coffee grounds and optimal carbonization time can produce briquettes with high energy potential, suitable for use as an alternative fuel.